2012
DOI: 10.1124/jpet.112.199935
|View full text |Cite
|
Sign up to set email alerts
|

Postexposure Application of Fas Receptor Small-Interfering RNA to Suppress Sulfur Mustard–Induced Apoptosis in Human Airway Epithelial Cells: Implication for a Therapeutic Approach

Abstract: Sulfur mustard (SM) is a vesicant chemical warfare and terrorism agent. Besides skin and eye injury, respiratory damage has been mainly responsible for morbidity and mortality after SM exposure. Previously, it was shown that suppressing the death receptor (DR) response by the dominant-negative Fas-associated death domain protein prior to SM exposure blocked apoptosis and microvesication in skin. Here, we studied whether antagonizing the Fas receptor (FasR) pathway by small-interfering RNA (siRNA) applied after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Non-coding RNA-based therapeutics are currently under investigation for treatment of lung diseases and pathologies including injury caused by mustards. Keyser et al (2013) analyzed the effects of siRNA targeting the Fas receptor (FasR) on the toxicity of SM in human bronchial/tracheal epithelial cells. FasR siRNA was found to inhibit SM-induced caspase 3 activation via the extrinsic pathway; this was associated with significant decreases in both apoptosis and necrosis.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Non-coding RNA-based therapeutics are currently under investigation for treatment of lung diseases and pathologies including injury caused by mustards. Keyser et al (2013) analyzed the effects of siRNA targeting the Fas receptor (FasR) on the toxicity of SM in human bronchial/tracheal epithelial cells. FasR siRNA was found to inhibit SM-induced caspase 3 activation via the extrinsic pathway; this was associated with significant decreases in both apoptosis and necrosis.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…A recent report has also demonstrated that the use of RNA interference against the Fas receptor, applied up to 8 hours postexposure in vitro, was able to significantly reduce apoptosis 24 hours after SM exposure. 24 This use of a highly selective antagonist of the Fas-mediated pathway of apoptosis added further evidence for an important role of this pathway in SM-induced apoptosis. Other proteins in the extrinsic apoptosis pathways (eg, cFLIP, DR-4, and DR-5) could play a role in SM-induced apoptosis.…”
Section: Apoptosis Inhibitorsmentioning
confidence: 91%
“…[5][6][7][8][9][10][11][12][13] The multiplicity of the different cellular components (DNA, proteins, thiol compounds, etc) and the pathways affected by SM have complicated the efforts to establish a clearly defined mechanism-based therapeutic approach for SM exposure. As schematically indicated in Figure 1, some of the toxic effects of SM and the half mustard (2-chloroethyl sulfide, CEES) include oxidative stress, [14][15][16][17][18][19][20] proinflammatory pathways, 21,22 apoptosis, 19,[23][24][25] and DNA damage. 26,27 In addition to these toxic effects, low-level exposure to SM causes weight loss and sensory irritation.…”
mentioning
confidence: 99%